2018
DOI: 10.1103/physrevlett.120.201103
|View full text |Cite
|
Sign up to set email alerts
|

Static Orbits in Rotating Spacetimes

Abstract: We show that under certain conditions an axisymmetric rotating spacetime contains a ring of points in the equatorial plane, where a particle at rest with respect to an asymptotic static observer remains at rest in a static orbit. We illustrate the emergence of such orbits for boson stars. Further examples are wormholes, hairy black holes, and Kerr-Newman solutions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…For a distant observer, this shell would look like a shadow similar to that of a black hole. The existence of static degenerated orbits in other spacetimes is considered in [38][39][40][41]. We note also that in SFNS spacetimes, as opposed to black holes, a freely moving massive particle with E ≥ 1 will inevitably escape to infinity, while such a particle with E < 1 will move on a bound geodesic; thus the value E = 1 separates bound and unbound orbits.…”
Section: Bound Orbitsmentioning
confidence: 95%
See 1 more Smart Citation
“…For a distant observer, this shell would look like a shadow similar to that of a black hole. The existence of static degenerated orbits in other spacetimes is considered in [38][39][40][41]. We note also that in SFNS spacetimes, as opposed to black holes, a freely moving massive particle with E ≥ 1 will inevitably escape to infinity, while such a particle with E < 1 will move on a bound geodesic; thus the value E = 1 separates bound and unbound orbits.…”
Section: Bound Orbitsmentioning
confidence: 95%
“…Thus, a bound orbit of the general type oscillates near a stable circular orbit (an oscillation is the motion from pericentre to apocentre and back) and ϕ osc is the angle between any two successive pericentre points of the orbit. The relativistic precession of pericentres of bound orbits is considered in [1,5,11,[40][41][42][43][44] both from a purely theoretical point of view and in the context of observations of S-stars in the Galactic Centre. If a massive test particle moves radially in some nonstatic degenerate orbit, which will be the case if J = 0 and A(r 0 ) < E 2 < 1, then ∆ ϕ = −2π.…”
Section: Bound Orbitsmentioning
confidence: 99%
“…In [58] is was shown that in stationary rotating spacetimes static orbits in the equatorial plane may exist. On this kind of orbit a particle stays at rest relative to an observer in the asymptotic region when it was at rest initially.…”
Section: G Ergosurface and Static Orbitsmentioning
confidence: 99%
“…The necessary and sufficient condition for a static orbit is that g tt possesses a local maximum (stable) or a local minimum (unstable) in some region where g tt < 0. It was demonstrated in [58] that static orbits exist for rotating boson stars and wormholes immersed in rotating matter. For symmetric wormhole solutions considered in this work g tt always is extremal at the throat.…”
Section: G Ergosurface and Static Orbitsmentioning
confidence: 99%
“…One of the most impressive recent examples in this context represents the discovery of hairy black holes based on boson stars [16,17]. Another recent surprise was the realization that rotating boson stars allow for static orbits [18].…”
Section: Introductionmentioning
confidence: 99%